2021
DOI: 10.3390/f12050618
|View full text |Cite
|
Sign up to set email alerts
|

Dropout Intention, Motivation, and Socio-Demographics of Forestry Students in Romania

Abstract: Reducing students’ dropout rate is a major challenge for universities. Based on a quantitative approach, this study aims to analyze and explain students’ dropout intention at the largest forestry school in Romania by collecting data in their first two months of the academic year prior to failing any courses. The study participants are undergraduate freshmen, male and female students, and the tools are psychological instruments commonly used or specifically developed for this study. Our findings partly confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…They refer to the student's social and economic circumstances, contributing to their failure to complete higher education. Prior literature [4,44,56,[72][73][74][75] depicts that family background (e.g., family's socioeconomic status and financial resources) as important predictors of students' dropout. Students whose parents have inferior educational qualifications are less likely to graduate, especially firstgeneration students [26,73,74].…”
Section: ) Socioeconomic Predictive Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…They refer to the student's social and economic circumstances, contributing to their failure to complete higher education. Prior literature [4,44,56,[72][73][74][75] depicts that family background (e.g., family's socioeconomic status and financial resources) as important predictors of students' dropout. Students whose parents have inferior educational qualifications are less likely to graduate, especially firstgeneration students [26,73,74].…”
Section: ) Socioeconomic Predictive Variablesmentioning
confidence: 99%
“…Prior literature [4,44,56,[72][73][74][75] depicts that family background (e.g., family's socioeconomic status and financial resources) as important predictors of students' dropout. Students whose parents have inferior educational qualifications are less likely to graduate, especially firstgeneration students [26,73,74]. According to Aina [56], students coming from disadvantaged educational families are at a higher risk of dropping out.…”
Section: ) Socioeconomic Predictive Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study on students enrolled in undergraduate forestry study programmes in Romania, Cocoradă et al . (2021) reported that perceived barriers to the completion of studies are based on student emotions, attitudes, and external factors. Poor programme choice not based on talent or preferences resulted in university students in forest-related programmes in Turkey being dissatisfied with their career opportunities and being unable to secure desired jobs (Yavuzaslan et al .…”
Section: Introductionmentioning
confidence: 99%